Performance analysis and improvement of rabin primitive based cryptosystems - Mahad, Zahari (2014)
In this study, we analyze the performance of a new cryptosystem called AAβ Public Key Cryptosystem. The encryption process for the AAβ cryptosystem is easy and fast as operations involved only add and multiply operations. While in the decryption process, it involves the mathematical solution method using Chinese Remainder Theorem that produces four different answers where only one correct answer need to be determined by user. The AAβ cryptosystem is constructed based on the mathematical problem of solving the Square Root Modulo and Integer Factorization problem. Results from the study and analysis found that AAβ cryptosystem have speeds exceeding RSA and ECC cryptosystem encryption process. While the decryption process, AAβ have speeds exceeding RSA and ECC. But when the sizes of prime number increase to 2048-bits, ECC is faster than AAβ. Through research and analysis, we have found a new feature in AAβ cryptosystem can be enhanced which can result in increased speed on the decryption process. Therefore, in this study, we will define an amended structure of the AAβ cryptosystem by improving existing features resulting in increased speed in the decryption process. With this new definition, we still maintain safety features available on AAβ cryptosystem to avoid being attacked by enemies. Finally, we amend the Rabin cryptosystem utilizing the encryption strategy of the AAβ algorithm and run experiments to gauge its efficiency.